PENGARUH BAURAN PEMASARAN JASA DAN KEPERCAYAAN PASIEN TERHADAP LOYALITASPASIEN (STUDI KASUS DI POLI SPESIALIS REMATOLOGI RUMAH SAKIT HASAN SADIKIN BANDUNG) - Indira Puspasari (Lembaga Penelitian Universitas Langlangbuana, 2020)
Competition of hospital specialists in the city of Bandung encourages health service facilities to become a socio business. It is required to gain the patient's trust becomes loyal to the hospital as a public service institution, handling strategic role to improve public health status and health service facility. There is an integrated specialist polyclinic consisting of subspecialists, including a rheumatology specialist poly. Hospital is a service business based on trust, morals and ethics. The effort to support the hospital business is the application of the marketing mix concept and patient trust. The concept of the hospital service marketing mix is ​​9 Ps, which consists of the elements: product, price, promotion, location, people, process, physical facilities, professional, performance /employee appearance. Patient trust is the key to marketing to foster patient loyalty to gain benefits for the hospital. The purpose of this research was to identify the service marketing mix, and patient trust in patient loyalty in rheumatology specialist poly of general hospitals in Bandung. The observation unit in patients in the rheumatology specialist poly in July 2020. the survey method used was descriptive, explanatory, data testing with path analysis techniques. The conclusion of this research shows that the increase in the performance of the marketing mix and trust can increase patient loyalty. Research results expected to be a reference for improving the performance of the marketing mix in hospitals and useful in developing economics, especially marketing management in hospitals.